5x-34+3x=-6(1-2x)

Simple and best practice solution for 5x-34+3x=-6(1-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-34+3x=-6(1-2x) equation:


Simplifying
5x + -34 + 3x = -6(1 + -2x)

Reorder the terms:
-34 + 5x + 3x = -6(1 + -2x)

Combine like terms: 5x + 3x = 8x
-34 + 8x = -6(1 + -2x)
-34 + 8x = (1 * -6 + -2x * -6)
-34 + 8x = (-6 + 12x)

Solving
-34 + 8x = -6 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
-34 + 8x + -12x = -6 + 12x + -12x

Combine like terms: 8x + -12x = -4x
-34 + -4x = -6 + 12x + -12x

Combine like terms: 12x + -12x = 0
-34 + -4x = -6 + 0
-34 + -4x = -6

Add '34' to each side of the equation.
-34 + 34 + -4x = -6 + 34

Combine like terms: -34 + 34 = 0
0 + -4x = -6 + 34
-4x = -6 + 34

Combine like terms: -6 + 34 = 28
-4x = 28

Divide each side by '-4'.
x = -7

Simplifying
x = -7

See similar equations:

| -4.5s-2=5.5s-4.2 | | 20x+2=142-38 | | 20x+2=142+38 | | 15y^2-15y=0 | | -4.45-2=5.5s-42 | | x^2-2x-(0.375)=0 | | m=7/8,(7,-3) | | 7.87-9.65x=8.52-3.21 | | 5f+7g=-35 | | 5x-19-3x+4=180 | | 5x-19+3x+4=180 | | 8x+9+x-6= | | XY-4y=9 | | n^2-2n+1=144 | | 18x+6y=28 | | 24-45t=16 | | 15x+2yx=-30 | | n^2+10n+25=64 | | 8x+6=4x+50 | | 2(x)+4(y)=196 | | n^2-22n+121=13 | | 2(5k-4)-27= | | 14(t-2)+7t=7(3t+3)-9 | | 17n+1=0 | | 35q=-175 | | -8x+y=28 | | 2(3x-2)=4(5x+3) | | 2.2x-4.5+x-2.1= | | 19-.4x=34 | | n^2-18n+81=5 | | 13e=-52 | | 36x+48=24-x |

Equations solver categories